Compressive Strength of Concrete with Nickel Carbon Sulfur and Dirty Sulfur Waste Substitution: A Unit Price Analysis (AHSP) Approach - Haryanto, Vian Marantha; Soeparyanto, Try Sugiyarto (Jurnal Locus Penelitian dan Pengabdian, 2025)
Nickel is one of the minerals that is in demand by many parties, especially now that nickel is an important ingredient in the promotion of green energy because it is a component of electric vehicle production. According to the International Energy Agency (IEA), nickel demand in 2020 is 2,340.56 metric tons and according to the sustainable development scenario, nickel demand is projected to reach 6,265.74 metric tons which can account for 60% of total clean energy in 2040. However, the impact of this mining is a case of environmental damage such as road damage, water pollution, air pollution, land damage. Based on the Regulation of the Minister of Environment and Forestry Number 6 of 2021 concerning Procedures and Requirements for the Management of Hazardous and Toxic Waste Materials, the determination of the status of B3 waste is carried out through characteristic tests which include explosive, flammable, reactive, infectious, corrosive and/or toxic. TCLP test, LD50 toxicology test and sub-chronic toxicology test were performed to determine the toxic properties of B3 waste. The method used in this study is a concrete mix design job as an advanced processing of cement/concrete manufacturing. This research is experimental where this research aims to determine the relationship between the compressive strength of concrete and the compression testing machine with the concrete mix design method. The test specimen made in this experiment was in the form of a concrete cylinder with a height of 300 mm and a diameter of 150 mm totaling 150 samples with a fermentation period of 7,14,28,54 and 90 days. Carbon sulfur and dirty sulfur are determined as non-B3 waste based on the results of the TCLP test so that further processing and utilization can be carried out. Carbon sulfur & dirty sulfur from the results of laboratory tests showed that the toxicity characteristics leaching procedure (TCLP) and total concentration (TK) values did not exceed the Category B threshold according to PP22 of 2021 so that it was non-B3 waste so that it could be utilized. For the 90-day fermentation period, the highest compressive strength is cs+ds 5%, cs+ds 10% of 179.4 kg/m², 170.3 kg/m². With an economic value for each Cs+Ds 5% of IDR 34,042.50, Cs+Ds of 10% of IDR 36,941.14 and Cs+Ds of 15% of IDR 39,495.52.